Risk Factors of HIV among Male Military Personnels: A Meta Analysis - Ayu Anulus; Bhisma Murti; Hanung Prasetya (Journal of Health Promotion and Behavior, 2019)
Background: Military personnel has a high risk of being exposed to HIV. The transmission of HIV from male military personnel is like an iceberg phenomenon. Based on studies in the US, UK, and France, the military personnel from these countries are much more likely to be contaminated with HIV than the equal age/sex group in the civilian population. This study aimed to analyze the risk factors of HIV among male military personnel by using meta-analysis.Subjects and Method: This study was a systematic and meta-analysis study. The articles used in this study were obtained from several electronic databases including PubMed, Scopus, Springer Link, ScienceDirect, and Clinical key. These articles were collected for 2 weeks. The keywords used in searching for the articles were as follows: "HIV", "soldier", "military", "armed force", "army", "navy", "air force", "armed force", "sex partner", "man having sex with man (MSM)", "homosexual", number of marriage","prostitute","sexually transmitted infection (STI)", and "conscription". The articles included in this study were full-text articles with cross-sectional design. The articles were collected using PRISMA flow diagram. These articles were analyzed using meta-analysis with the Review Manager 5.3 application.Results: MSM (aOR= 9.37; 95%CI= 5.31 to 16.55; p <0.001), sexually transmitted infections (aOR = 3.75; 95%CI= 3.00 to 4.68; p<0.001), sexual partners> 10 (aOR= 3.05; 95 CI= 2.12 to 4.38; p<0.001) increased the incidence of HIV among male military personnel, and it was statistically significant. Sex with CSWs (aOR= 3.93; 95% CI= 0.93 to 16.62; p= 0.060) increased the incidence of HIV among male military personnel, but it was not statistically significant.Conclusion: MSM, STI, and sexual partners >10 increase the incidence of HIV among male military personnels.Keywords: HIV, MSM, commercial sex workers, sexually transmitted infection, CSW, militaryCorrespondence: Ayu Anulus. Masters Program in Public Health. Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: anulusayu@gmail.com. Mobile: 082359056395.Journal of Health Promotion and Behavior (2019), 4(3): 178-188https://doi.org/10.26911/thejhpb.2019.04.03.03